HUBUNGAN TINGKAT KECANDUAN GADGET DENGAN KECERDASAN EMOSIONAL REMAJA DI SMA NEGERI 2 DOLOK SANGGUL TAHUN 2019 - Rani Kawati Damanik; Ester Saripati Harianja; Galvani Volta Simanjuntak; Tresa Mona Tamara Hutabarat (Jurnal Reproductive Health, 2019)
Gadgets addiction is a behavior of someone who can not control themselves in the use of gadgets that cause individual dependence. This can harm someone especially teenagers. Emotional intelligence is the ability to recognize our own feelings and the feelings of others. The purpose of this study was to analyze the relationship between the level of gadget addiction and emotional intelligence of adolescents at State Senior High School 2. This research is a correlation analysis study with cross sectional design. The research population involved students of class XI IPS at State Senior High School 2. The samples in this study involved 84 people taken with proportional random sampling techniques. The results showed the majority of gadget addiction levels were mild (34,5%), moderate category (63,1%), and heavy categories (2,4%) and the level of emotional intelligence with normal categories (10,7%), borderline categories (81,0%), abnormal categories (8,3%). Spearman's Test Results with a = 0.05 with a p value = -0,037, it can be concluded that there is relationship between the level of gadget addiction and emotional intelligence on students at State Senior High School 2. Suggestions for students at State Senior High School 2 to be better in using gadgets in their free time, so as not to interfere with daily activities